Pickup of thermal non-equilibrium ions by a low-frequency Alfvén wave via nonresonant and stochastic interaction. Issue 10 (15th November 2015) - Liu, Hai-Feng; Tang, Chang-Jian; Zhang, Xin; Zhu, Li-Ming; Zhao, Yong
Abstract The nonresonant and stochastic heating of ions with a Kappa (<alternatives><inline-graphic xlink:href="ark:/27927/pgkjcpc2sp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />κ</alternatives>) velocity distribution by an Alfvén wave is investigated by means of both extremum method and test-particle simulation. Due to energetic-ion population, <alternatives><inline-graphic xlink:href="ark:/27927/pgkjcpc2sp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />κ</alternatives> ions are picked up in the perpendicular (to the background magnetic field) direction via wave-ion nonresonant interaction and the ion energy gain depends on the thermal non-equilibrium factor (κ factor) and the ratio of the wave electric-field energy to background magnietic-field energy. With heating ion in perpendicular direction, the stochastic heating is to be sufficient and the maximal average parallel ion speed is the Alfvén wave velocity, independent of initial ion velocity distribution. This phenomenon may have relevance to the heating in the solar wind, and there is a close link between heating, differential flow, and temperature anisotropy.